Mixed T Helper1/T Helper2/T Cytotoxic Profile in Subjects with Chronic Chagas Disease with Hypersensitivity Reactions to Benznidazole - Melisa D. Castro Eiro; María A. Natale; María G. Alvarez; Araceli Castro; Débora Seigelshifer; Rodolfo Viotti; Marisa Fernández; Luis Mazzuoccolo; Bruno Lococo; Graciela L. Bertocchi; Gonzalo Cesar; María C. Albareda; et al. (Microbiology Spectrum, 2022)
ABSTRACT Dermatitis is the most common adverse event during treatment with benznidazole in chronic Chagas disease and is probably mediated by T cells. A set of molecules representative of the different type IV hypersensitivity reactions was evaluated in the circulation and skin biopsies of Trypanosoma cruzi-infected subjects presenting dermatitis during benznidazole administration. Through cytometric bead assays and enzyme-linked immunosorbent assay capture techniques, the serum levels of cytokines, chemokines, proapoptotic molecules, and mediators of the activation and migration of eosinophils and T cells were measured in subjects infected with Trypanosoma cruzi who exhibited skin adverse events (n = 22) and compared with those without adverse events (n = 37) during benznidazole therapy. Serum levels of interleukin- 5 (IL-5), soluble Fas cell surface death receptor ligand (FAS-L), and interferon γ-induced protein (IP-10) significantly increased at 7 to 30 days posttreatment with benznidazole and decreased thereafter in subjects with dermatitis but not in those without dermatitis. Circulating eotaxin levels were lower in subjects with dermatitis than in those without. Two patterns emerged in the skin biopsies: a T helper 1/T cytotoxic profile and a T helper 2/T cytotoxic profile with the presence of CD4+ and CD8+ T cells. Increased low-density lipoprotein (LDL), glutamic-oxaloacetic transaminase (GOT), uremia, and T cell activation emerged as risk factors for the development of dermatitis during benznidazole administration. These results support a delayed-type hypersensitivity reaction to benznidazole, involving CD4+ and CD8+ T cells and eosinophils, and a mixed cytokine profile. This study provides new insights for better management of adverse drug reactions to benznidazole. IMPORTANCE This study identified the risk factors for the development of adverse reactions to benznidazole and identified a set molecule to monitor the appearance of these reactions. This knowledge might improve the safety of benznidazole administration.